2022
DOI: 10.1039/d2se00282e
|View full text |Cite
|
Sign up to set email alerts
|

A two-dimensional perovskite oxyfluoride Pb3Fe2O5F2 as a catalyst for electrochemical oxidation of water to oxygen

Abstract: A two-dimensional (2D) perovskite oxyfluoride Pb3Fe2O5F2, deposited on a conductive glass substrate, exhibited activity for electrochemical oxidation of water. This 2D oxyfluoride electrode could oxidize water forming O2 at a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Simondson et al reported CoFePbO x as an efficient and stable OER catalyst in acidic electrolytes at elevated temperatures . Mizuochi et al reported a two-dimensional perovskite oxyfluoride Pb 3 Fe 2 O 5 F 2 , deposited on a conductive glass substrate, as an OER catalyst at +1.7 V vs the reversible hydrogen electrode (RHE) with a faradaic efficiency of almost unity . Under acidic conditions, the stability of the catalysts is significantly influenced by the presence of Pb in various composites.…”
Section: Introductionmentioning
confidence: 99%
“…Simondson et al reported CoFePbO x as an efficient and stable OER catalyst in acidic electrolytes at elevated temperatures . Mizuochi et al reported a two-dimensional perovskite oxyfluoride Pb 3 Fe 2 O 5 F 2 , deposited on a conductive glass substrate, as an OER catalyst at +1.7 V vs the reversible hydrogen electrode (RHE) with a faradaic efficiency of almost unity . Under acidic conditions, the stability of the catalysts is significantly influenced by the presence of Pb in various composites.…”
Section: Introductionmentioning
confidence: 99%